Some Emerging Research Areas in Marketing (Global Journal of Management and Business Research, 2012)
The purpose of this study is to explore the emerging research areas in marketing. The literature from the various journals is reviewed to find out the evidence from different contexts that which areas are gaining the attention of researchers. On the basis of literature review, the first part of study explains how to find out an emerging research area in particular discipline as well as emerging trends in research in different areas of marketing. 2nd part the study focuses on the theory development and argues that the theory development in marketing has been neglected throughout in different paradigms of management. And at the end the remarks of the authors are concluded.